A new medical pluralism? : alternative medicine, doctors, patients, and the state - Cant, Sarah, 1965- (UCL Press ; Distributed in North America by Garland Pub., 1999)
This comparative text examines the rise of non-orthodox medicine and theorizes the changing nature of health care in modern societies. It engages with sociological debates on modernity and postmodernity, anthropological work.